2013
DOI: 10.1007/s00441-013-1675-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of novel binocular colour, motion and contrast tests in glaucoma

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. The effects of glaucoma on binocular visual sensitivity for detection of different stimulus attributes were investigated at the fovea and in four paracentral retinal regions. The study employed a number of visual stimuli designed to isolate the processing of different stimulus attributes. We measured absolute contrast detection thresholds and functional contrast sensitivity using Landolt ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Obviously, the most affected area of functional connectivity was located in the ventral pathway in Dai’s study; the dorsal pathway changed little. However, clinical features indicate injury to both visual pathways [27]. This contradiction arises from the method by which functional connectivity is measured.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the most affected area of functional connectivity was located in the ventral pathway in Dai’s study; the dorsal pathway changed little. However, clinical features indicate injury to both visual pathways [27]. This contradiction arises from the method by which functional connectivity is measured.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the current study shows statistically significant correlations between L CCTs and M CCTs (r ¼ 0.42, P < 0.05) and M CCTs and S CCTs (r¼ 0.48, P < 0.05) in eyes affected by glaucoma. Using the Color Assessment Test by Birch et al, 16 Rauscher et al 23 found that redgreen loss is almost as common as blue-yellow loss in glaucoma patients. Our current results also imply a correlation between red-green and blue-yellow loss in glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most obvious is the greater reduction in the contribution short-wavelength light makes to retinal illuminance with increasing age and hence the more rapid increase in YB thresholds above 40 years of age. If the loss of RGC axons during the life span accounts for much of the increase in RG and YB thresholds observed in normal aging, accelerated loss of RGC axons and cell bodies as documented in glaucoma (Marvasti, Tatham, Zangwill, Girkin, Liebmann, Weinreb, and Medeiros, 2013]) may be directly linked to the corresponding increase in color thresholds that has also been shown to depend on retinal topography (Rauscher et al, 2013). Further work is needed to establish whether the severity of localized RG and YB color loss in glaucoma can be used to estimate directly the percentage of ganglion cells lost or the rate of progression in glaucoma.…”
Section: Processes That May Contribute To Color Vision Changes In Normentioning
confidence: 99%